Expert opinion: Stepwise ultrasound assessment of suspected placenta accreta spectrum using 2D, Doppler and 3D imaging. (March 2022) - Srinivasan, D.; Shaw, C.J.; Dall'Asta, A.; Papanikoloau, K.; Yazbek, J.; Lees, C.C.
Abstract: Placenta Accreta Spectrum (PAS) describes a spectrum of conditions ranging from 'sticky' placenta to placenta accreta, increta and percreta-each describing progressively deeper invasion into the uterus. It is a major contributor to maternal and perinatal morbidity particularly where clinical facilities are not immediately available. Hence accurate diagnosis is important in determining timing and place of delivery, and logistical arrangements of the clinical team and specialties. Although many different ultrasound features have been described, their relationship to the final operative diagnosis remains variably described. Ultrasound manufactures have developed new imaging techniques particularly in relation to Doppler and 3D processing techniques. We describe a standardized imaging approach employing new ultrasound modalities matched to the attributes unique to invasive placenta. The '3V' system describes the stages of placental invasion: namely low-flow Doppler techniques to delineate the vascular anatomy of the placenta and delineating its interface with the myometrium, and 3D 'context preserving' post processing technologies defining the placental interface with maternal structures (vesicular invasion and visceral extension). Used together with well characterized 2D imaging signs, we describe pictorially by reference to clinical cases how this standardized methodology allows new insights into the ultrasound diagnosis of PAS.